THE EFFECT OF INTERNAL AND EXTERNAL ACCOUNTABILITY, JOB MOTIVATION AND EDUCATION ON LOCAL GOVERNMENT OFFICIAL’S PERFORMANCE - Kathleen Asyera Risakotta; Rusdi Akbar (Faculty of Economics and Business, Universitas Gadjah Mada, 2018)
This study aims to empirically analyze the influence of internal and external accountabilities, job motivation and education on the performance of local government officials with organizational commitment as the intervening variable. This study used a mixed method that consists of Partial Least Square (PLS) for the analysis of the quantitative and a thematic content analysis for the qualitative approach. The sample includes 224 government officers from the Provincial Government of Maluku Province and Ambon City Council. The result of this study shows that internal accountability, job motivation and organizational commitment have a positive influence on the performance of the local government employees, while both external accountability and education do not play a positive role in their organizational commitment. These are the driving factor for organizations to improve the accountability and performance of government institutions, so that good governance may occur in the future. The results of this study could be used as advices to local governments on their employee training programs in order to improve the performance of the employees of local government agencies.